KEKERASAN VERBAL DALAM TALK SHOW INDONESIA LAWYERS CLUB (ILC) DI TVONE - Novinasari, Ida Ayu Putu (Humanis, 2016)
Verbal violence can be found anywhere and occur at anytime during the process of communication. It can also be found in the television programs, such as talk show. One of talk show which showed indications of verbal violence is Indonesia Lawyers Club (ILC) on tvOne. The theory of pragmatics, theory of sentence, and the Pateda’s theory of language usage is used in this research on verbal violence in Indonesia Lawyers Club (ILC). Methods and techniques used in this research consist of three, namely 1) “simak” method for data collection, 2) method of meaning interpretation for data analysis, and 3) formal and informal method for presentation. Thus, the results obtained from this research are (1) verbal violence in the form of declarative sentences, imperative sentences, and interrogative sentences; (2) verbal violence in the speech acts: assertives, directives, commissives, and expressives; (3) types of verbal violence that occur in the Indonesia Lawyers Club (ILC), namely satire, accusations, rejection, suspicion, criticism, protest,  insults, mockery, decision, and duress; (4) factors that affect the occurrence of verbal violence: factor in the desire to convey something, moods, environmental situation, circumstances, social level, and age.
Keywords: verbal violence, talk show, sosiopragmatic